FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI PATCH BUKAL MUKOADHESIF ESTRAK CENGKEH (Syzygium aromaticum L.) DENGAN KOMBINASI POLIMER POLIVINIL PIROLIDON (PVP) DAN NATRIUM KARBOKSIMETIL SELULOSA (NA-CMC) TERHADAP BAKTERI Streptococcus mutans - Vina Purnamasari; Iskandar Zulkarnain (Fakultas Farmasi UMI, 2018)
Clove extract (Syzygium aromaticum) contains eugenol 70% - 85%. The clove extract is formulated in the form of mucoadhesive buccal patches. The purpose of this study was to obtain the formulation for mucoadhesive buccal patches having optimal stability that has good pharmaceutic properties and also effectively inhibits the Streptococcus mutans bacteria. The research design used was laboratory experimental research. The mucoadhesive buccal patches with a combination of PVP and HPMC polymers made in 5 formulas based on their concentration, formula 1 1% Na-CMC concentration, formula 2 2% Na-CMC concentration, formula 3 2% PVP concentration, formula 4 3% PVP concentration, formula 5 combination of Na-CMC and PVP with concentrations of 1% and 2%. Patches obtained were tested for physical properties including organoleptic examination, surface tension, weight uniformity, thickness uniformity, folding endurance and pH patch surface. The patch is also tested for its antimicrobial power by measuring the zone of bacterial resistance. The results showed that the buccal patches of clove extract produced a dark brown color with opaque transparency, smooth surface texture with a patch weight of around 66.67 mg - 140.67 mg, standard deviation of patch thickness around ± 0.009 - ± 0.058, folding endurance more than 300 times, surface pH ranged from 6.40 - 6.60, and antimicrobial activity shows that all patch formulations can inhibit the growth of Streptococcus mutans bacteria to prevent dental caries, but the formula that has the largest inhibition zone was formula IV with a inhibition zone of about 1.667 cm.